IMPLEMENTASI TECHNOLOGICAL PEDAGOGICAL CONTENT KNOWLEDGE SEBAGAI MODERNISASI DI BIDANG PENDIDIKAN - Nayla Rizqiyah (Fakultas Ekonomi Universitas Negeri Medan, 2021)
Technological pedagogical content knowledge (TPACK) is a relatively new learning model in the world of education. The practice of implementing this method includes mastery of technology, pedagogy and knowledge of learning content. TPACK is involved in the process of compiling learning designs, learning models and strategies, assessing and rearranging connected curricula and making technology the basis of reference for educational development. The research was carried out randomly on college students and the results of the research were described using a qualitative descriptive method. The relationship between TPACK and modernization in the world of education are two inseparable things, the inclusion of technology in elements of Indonesian education has had a significant effect and has changed the conventional order with a new order of methods and is expected to bring Indonesian education to a more advanced direction. It is hoped that research can provide benefits for developing the field of the education system as well as as additional information for other research.